COMPARATIVE ANALYSIS USES WEIGHTED PRODUCT (WP) AND SIMPLE ADDITIVE WEIGHTING (SAW) METHODS IN THE BEST GRADUATION SELECTION SYSTEM - Agus Sidiq Purnomo; Anief Fauzan Rozi (STMIK Widya Cipta Dharma, 2019)
Determination of students in the Study Program of the Information System of Mercu Buana University in Yogyakarta is still in the process of the decision. This is because it has not maximized the use of technology to use existing data in decision making. This assessment uses 6 criteria that are used as parameters in conducting experiments, in order to make the right decisions in this study, namely Multiple Attribute Decision Making(MADM) Simple Additive Weighting (SAW) and Weighted Product (WP). Based on the data that has been tested using the system, the system can be used properly by ranking results based on the highest value. The test results for the speed of access time obtained values of 1362.90 ms for SAW and 672.60 ms for WP. While the test results using Relative Standard Deviation (RSD) obtained a value of 8,2004 for SAW and 10.1868% for WP. In this case using the WP method is more because it is more optimal.